Dilemmas of nudging in public health: an ethical analysis of a Danish pamphlet. (26th December 2020) - Busch, Jacob; Madsen, Emilie Kirstine; Fage-Butler, Antoinette Mary; Kjær, Marianne; Ledderer, Loni
Summary: Nudging has been discussed in the context of public health, and ethical issues raised by nudging in public health contexts have been highlighted. In this article, we first identify types of nudging approaches and techniques that have been used in screening programmes, and ethical issues that have been associated with nudging: paternalism, limited autonomy and manipulation. We then identify nudging techniques used in a pamphlet developed for the Danish National Screening Program for Colorectal Cancer. These include framing, default nudge, use of hassle bias, authority nudge and priming. The pamphlet and the very offering of a screening programme can in themselves be considered nudges. Whether nudging strategies are ethically problematic depend on whether they are categorized as educative- or non-educative nudges. Educative nudges seek to affect people's choice making by engaging their reflective capabilities. Non-educative nudges work by circumventing people's reflective capabilities. Information materials are, on the face of it, meant to engage citizens' reflective capacities. Recipients are likely to receive information materials with this expectation, and thus not expect to be affected in other ways. Non-educative nudges may therefore be particularly problematic in the context of information on screening, also as participating in screening does not always benefit the individual.